1997
DOI: 10.1038/bjc.1997.297
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hyperthermic potentiation of cisplatin action in cisplatin-sensitive and -resistant tumour cells

Abstract: Summary In this study, the mechanism(s) by which heat increases cis-diamminedichloroplatinum (cisplatin, cDDP) sensitivity in cDDPsensitive and -resistant cell lines of murine as well as human origin were investigated. Heating cells at 430C during cDDP exposure was found to increase drug accumulation significantly in the cDDP-resistant cell lines but had little effect on drug accumulation in the cDDP-sensitive cell lines. DNA adduct formation, however, was significantly increased in all cell lines studied. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 24 publications
1
24
0
3
Order By: Relevance
“…In addition, at 40-428C, neoplastic cells become more chemosensitive due to an increase in the intracellular concentration of drugs and in their activation process, especially for alkylating agents, and to alterations in the DNA repair process [23,24]. It has been demonstrated that the formation of platinum-DNA adducts after cisplatin exposure in hyperthermic conditions is enhanced and/or adduct removal is decreased in heated cells, resulting in relatively higher DNA damage [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at 40-428C, neoplastic cells become more chemosensitive due to an increase in the intracellular concentration of drugs and in their activation process, especially for alkylating agents, and to alterations in the DNA repair process [23,24]. It has been demonstrated that the formation of platinum-DNA adducts after cisplatin exposure in hyperthermic conditions is enhanced and/or adduct removal is decreased in heated cells, resulting in relatively higher DNA damage [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…[23] Cisplatin is a drug that is retained in the peritoneal cavity and its penetration into the adjacent tissues is potentiated by heat in both platinum sensitive and platinum resistant cells lines. [78] The ideal dose of cisplatin has being evaluated in the CHIPASTIN trial. This phase I-II escalating dose trial established that the use of 70 mg/m2 of cisplatin for one hour at 42°C was the most appropriate protocol (Clinical Trials identifier: NCT02217956).…”
Section: Hipec Methodology and Drugsmentioning
confidence: 99%
“…Our experience of IPCH shows that the device is safe and reliable for patients with peritoneal carcinomatosis, so we tried this method in the pleural cavity (Gilly et al, 1999). We choose MMC and CDDP because their antitumor effects and intraperitoneal or pleural pharmacokinetics are highly predictable and have been studied most extensively (Rusch et al, 1999;Matsuzaki et al, 1995;Hettinga et al, 1997;Ratto et al, 1999).…”
Section: Discussionmentioning
confidence: 99%